One-step synthesis of γ-Fe2O3/Fe3O4 nanocomposite for sensitive electrochemical detection of hydrogen peroxide. (20th February 2021) - Molodtsova, Tatyana; Gorshenkov, Mikhail; Saliev, Alexey; Vanyushin, Vladislav; Goncharov, Igor; Smirnova, Nina
Highlights: γ-Fe2 O3 /Fe3 O4 was prepared using pulse alternating current technique. The mechanism for the γ-Fe2 O3 /Fe3 O4 formation цф proposed. The γ-Fe2 O3 /Fe3 O4 sensor exhibited excellent properties for H2 O2 sensing. Abstract: Maghemite/magnetite nanocomposite (γ-Fe2 O3 /Fe3 O4 ) was prepared via an electrochemical method using pulse alternating current and applied for electrocatalytic reduction and sensing of hydrogen peroxide. The structural and compositional analysis of the γ-Fe2 O3 /Fe3 O4 was characterized by XRD, SEM, TEM and XPS. Its thermal decomposition behavior was studied using TG/DSC. The mechanism for γ-Fe2 O3 /Fe3 O4 nanocomposite formation was proposed. Furthermore, the H2 O2 sensing performance of the γ-Fe2 O3 /Fe3 O4 nanocomposite was evaluated in 0.1 M KH2 PO4 . The sensor exhibited a fast electron transfer process in γ-Fe2 O3 /Fe3 O4 nanocomposite. The optimized H2 O2 sensor revealed a remarkable low limit of detection of 0.05 μM, a wide linear range from 0.0002 to 8 mM, and a fast response time of 2 s. These results demonstrated that γ-Fe2 O3 /Fe3 O4 prepared via an electrochemical method using pulse alternating current is a promising efficient material for electrochemical sensing of H2 O2 . Graphical abstract: Image, graphical abstract